Inclusive education in the Netherlands: how funding arrangements and demographic trends relate to dropout and participation rates. Issue 11 (2nd November 2018) - Gubbels, Joyce; Coppens, Karien M.; de Wolf, Inge
ABSTRACT: There is a global trend towards including children with special needs in mainstream schools instead of placing them in special schools. However, the numbers of students in special schools varies greatly among regions due to variations in educational systems, funding arrangements – and the incentives that are associated with these arrangements – and demographic trends. In the Netherlands, a new policy aimed at inclusive education was introduced in 2014, together with financial measures to equalise funding for students with special needs across the country. The present study explored the effects of this equalisation policy, as well as the demographic trend of population decline, on dropout rates and participation rates in special education (namely, special schools for mainstream education and schools for special education). The data were retrieved from nation-wide registration systems. The results showed that population decline did not affect participation rates in special education, whereas decreases in funding did result in greater declines in participation rates in special education. Moreover, decreases in funding also resulted in higher dropout rates in areas with growing student populations. Although the reform of funding arrangements resulted in lower participation in special education, higher dropout rates might be a cost of this shift towards inclusive education.